De la région ressource au territoire ressource ? Réflexion autour de l’hydroélectricité communautaire au Lac-Saint-Jean (Québec) - Lucas Durand (Éditions en environnement VertigO, 2021)
Canadian rural areas are often qualified as resource regions. They are characterized by an extractivist development model and the presence of exogenous companies exploiting natural resources. We analyse the conditions of the emergence for a territorial appropriation of natural resource and an alternative regional development model: the resource territory. We base out point on the cas study of mini hydroelectric power stations, located in Lac-Saint-Jean region in Quebec Province. developed and managed by local municipal authorities and the ilnu community from Mashteuiatsh, with a territorial development objective.